Advances in Polymeric Nanofiltration Membrane: A Review. Issue 8 (24th May 2017) - Tul Muntha, Sedra; Kausar, Ayesha; Siddiq, Muhammad
ABSTRACT: The nanofiltration membrane was first introduced during late 1980s possessing properties between reverse osmosis and ultrafiltration membrane. Nanofiltration membranes have been used for applications including food industry, pharmaceutical, wastewater treatment, and desalination. This review presents an inclusive outlook of recent research and advances in polymeric nanofiltration membrane technology. Various methods were reported for nanofiltration membrane preparation particularly through electron beam irradiation, UV/photografting, layer by layer, plasma treatment, interfacial polymerization, and nanoparticle incorporation. Nanofiltration membranes were reported to remove microorganisms, turbidity, dissolved salts, and hardness. Major problem in application is nanofiltration membrane fouling, thus efforts regarding fouling mitigation are discussed. GRAPHICAL ABSTRACT: